EFFECTS OF BARLEY PROCESSING ON THE BIOPRODUCTIVE INDICES IN FATTENING THE WEANED LAMBS (NOTE II SMALL PARTICLES) - S. VOIA; GH. BOGDAN; D. DRINCEANU; I. PĂDEANU; S. DĂRĂBAN; I. SAUER; MIHAELA IVAN (Scientific Papers Animal Science and Biotechnologies, 2023)
The objective of our researches was to observe the nutritive and productive effect of the ratio, offered at discretion, composed of alfalfa hay and barley under the following presentation forms: whole grains, small particles ground (2.5mm) with and without addition of yeast, strain Yea-Sacc1026, to lambs submitted for fattening. The experiment lasted 37 days, the biological material was represented by Turcana lambs, grouped in three lots (n=11). Growth performances were insignificant (p> 0.05) for the final body weight, total weight gain and average daily gain, but the specific intake was decreased with 0.85 UNC in lambs that consumed ground barley prior to those that consumed whole barley grains. The addition of Saccharomyces cerevisiae, strain Yea-Sacc1026 in the ground barley at 2.5 mm has a significant effect (p<0.006) regarding total weight gain and average daily gain compared to the lambs fed with whole barley grains, with a specific intake lower with 1.21 UNC.